Didactic Interactions in Blended Learning: Dynamics of Knowledge Construction - Turpo-Gebera, Osbaldo; Diaz-Zavala, Rocio; Gutiérrez-Salcedo, Eduardo Luis; Delgado-Sarmiento, Yvan; Gonzales-Miñán , Milagros (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The study examines a Blended Learning course to identify patterns of didactic interaction that facilitate knowledge construction and, consequently, learning. The research reveals a transition towards virtuality from in-person interactions, gradual acquisition of learning, and a focus on autonomy. These transitions indicate greater development of significant content in virtual environments, suggesting a relationship between intensified virtual interaction, learning, and reduced dependence on the teacher. The analysis of educational practice in Blended Learning promotes autonomy, achievements, and participation through peer collaboration and increased social interaction, leading to notable outcomes.